Epistemologi, ontologi, dan aksiologi dalam ilmu sosial: Landasan filsafat untuk memahami perubahan masyarakat - musya, fatir riyachul; LABIBA, CHAYARA ELYA RAMEIZA; Achmad, Zahara Fajaria (Maliki Interdisciplinary Journal, 2026)
This article discusses the role of philosophy of science through its three main foundations, namely epistemology, ontology, and axiology, in understanding social change. Philosophy is understood as the basis of scientific thinking that helps humans discover truth, understand reality, and evaluate the usefulness of knowledge in social life. Epistemology examines the sources, methods, and validity of knowledge; ontology studies the nature of existence and the objects of knowledge; while axiology emphasizes values, ethics, and the benefits of knowledge for human life. These three branches of philosophy are interconnected and serve as the foundation for understanding continuously developing social dynamics. Social change can occur through evolution or revolution and is influenced by internal factors such as the development of science, technology, social conflict, and population growth, as well as external factors such as globalization and natural disasters. From a philosophical perspective, social change is viewed as an unavoidable process because society continuously experiences transformations in social relations, political systems, culture, and social structures. Therefore, philosophy of science plays an important role in shaping critical, systematic, and reflective thinking in order to understand social phenomena comprehensively. Thus, epistemology, ontology, and axiology become essential foundations for explaining social change scientifically and philosophically.